PENGARUH PINJAMAN PNM MINGGUAN TERHADAP KEUANGAN RUMAH TANGGA: ANALISIS DARI PERSPEKTIF EKONOMI, SOSIAL, DAN HUKUM - Angel Sophia Intan; Aliya jazila; Cyce cahyati; Siti elvia; Julita riani; Abdul Wafa Hidayatullah; Refli Kaldi; Riko Saputra; Nabila El Meidio; Auzai Rades Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the impact of PNM weekly loans on household finances from economic, social, and legal perspectives. The background highlights the role of microfinance in improving the welfare of low-income families, particularly women micro-entrepreneurs. This research employed a qualitative approach using interviews and observations with 20 loan recipients in rural areas. The findings reveal that from the economic perspective, 75% of respondents used loans to increase business capital and productivity, resulting in a 25–35% rise in monthly turnover. From the social perspective, 80% experienced stronger group solidarity and greater confidence in household financial decisions, though 25% reported social pressure due to late repayments. From the legal perspective, program implementation was found to be 100% compliant with OJK regulations and the Consumer Protection Law, with internal mediation resolving 90% of potential disputes.Overall, PNM contributes positively to household economic growth, women’s social empowerment, and legal compliance, though financial literacy and risk management still need strengthening for sustainable impact.